Harnessing genetic, chemical, and transcriptomic analyses guided the selection of Cistus creticus subsp. creticus genotypes rich in labdane-type diterpenes - Stefanos Kostas; Symela Ntoanidou; Christos Bazakos; Eirini Sarrou; Nausica Rafailidou; Antigoni Papanikolaou; Antonios Makris; Aikaterini-Angeliki Kotoula; Efstathios Hatziloukas; Athanasios Economou; Angelos K. Kanellis (Planta, 2026)
Main conclusion The present study connects the genetic diversity of Cistus creticus to its chemical profile, identifying elite genotypes and key biosynthetic genes for enhancing the production of valuable labdane diterpenes. Abstract Cistus creticus , a Mediterranean shrub, is known for its resin ladano, which is rich in pharmacologically active labdane-related diterpenes (LRDs). However, the genetic and molecular basis for the LRDs content variation among natural populations remains uncharacterized. This study aims to fulfill this lacuna by investigating a potential link between genetic diversity and chemotypic profile across 91 genotypes from seven different populations across Greece and identifying elite germplasm by uncovering the molecular and regulatory mechanisms underlying LRDs biosynthesis. The genetic analysis, employing ISSR markers, revealed significant genetic differentiation among populations (Φ ST = 0.294) that mirrored distinct chemotypic profiles. Genotypes clustered by origin with Chalkidiki and Sises being the most homogenous, high-yielding, and superior in LRDs production. The transcriptomic analysis of low (C1) vs. high (C18) LRDs genotypes identified 24,489 up-regulated genes, including key diterpene synthases [labda-7,13-dien-15-ol synthase ( LDDS2 ), ent -copalyl diphosphate synthase, copal-8-ol diphosphate synthase ( CLS )] and numerous transcription factors among which WRKY, bHLH and bZIP were strongly correlated with LRD accumulation. This work provides an initial representation of the regulatory landscape by identifying elite genotypes, key biosynthetic genes, and transcription factors linked to specific LRDs for promising breeding programs, future targeted experiments, and metabolic engineering.

The histone acetyltransferase GCN5 and the transcriptional coactivator ADA2b affect leaf development and trichome morphogenesis in Arabidopsis - Jenna Kotak; Marina Saisana; Vasilis Gegas; Nikoletta Pechlivani; Athanasios Kaldis; Panagiotis Papoutsoglou; Athanasios Makris; Julia Burns; Ashley L. Kendig; Minnah Sheikh; Cyrus E. Kuschner; Gabrielle Whitney; et al. (Planta, 2018)